15 years of Rev Rene - a tribute to the Brazilian Nursing! - Erdmann, Alacoque Lorenzini (Rev Rene, 2015)
Congratulations to Rev Rene, Northeastern Nursing Network Journal (in Portuguese), for its fifteen years of existence consecrating important contributions to the science and profession of nursing. Congratulations to the Postgraduate Program in Nursing, to the Nursing Department and to the institution Federal University of Ceará that hosts this important structure of scientific dissemination.